Advance Hydraulic Calculation of Fish Ladders, Sebesel River, Romania. - Robert Florin BEILICCI; Erika Beata Maria BEILICCI (Aerul şi Apa: Componente ale Mediului, 2022)
Sebesel 2 hydropower development is located on the Sebesel river, in the outskirts of Borlova, Caraș - Severin County. The realization of the fish ladder will not influence the flow regime of surface or groundwater in the neighboring area. The fish ladder is dimensioned to allow the migration of the ichthyofauna upstream during the spawning period and the partial transit of the alluviums as well as the downstream provision of a servitude flow Q = 0.066 mc / s. The Sebeșel 2 hydroelectric power plant is a hydropower arrangement by shunt without accumulation lake. The plant has 2 (two) power groups equipped with Pelton turbines. The power delivered by MHC Sebesel 2 is 792.31 kW. The installed flow rate is 0.80 m3 / s; gross fall: 120 m; capture rate 573 mdMN. The fish ladders are of the technical ladder type with pools. The objectives of the studies were: to describe the qualitative and quantitative structure of benthic invertebrate and fish macro communities; assessment of the ecological status of the rivers in the areas of hydropower development; highlighting the presence of fish species of conservative interest and assessing the status of their populations. The methodology was carried out in accordance with the provisions of the Water Framework Directive, Annex V used considered the following: Assessment of the status of aquatic communities; description of the structure of fish communities; assessment of the ecological status of the river sectors. The study led to obtaining some essential information for the exploitation and maintenance of the micro-hydroelectric plant as well as the fish ladder.